La Filosofía Política Sintética del Carácter de Producción - Bernal Mora, Héctor (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The Political Philosophy of the Character of Production, stimulus-sense, orientation as an original theoretical paradigm, allows for the synthesis of different irreconcilable and opposite points of view. In one way or another, all philosophies of history, or their corresponding components, fit into orientation. World history is orientation, product of the interaction of oriented men or groups of humans, who interpret the interpretation of the productive system itself, which is, in turn, the result of the interpretation of the interpretation of the previous system, the world they create and which, in turn, creates them. Man builds his world motivated, oriented, initially, the theory of political philosophy.